5PSQ-215 Clinical risk management through the 'unit dose' system. (14th March 2021) - Corridoni, S; Sorice, P; Armillei, L; Pizzica, S; Cinalli, C; Gasbarri, F; Di Florio, G; Romagnoli, A; Auriemma, L; Costantini, A
Abstract : Background and importance: In clinical practice, the unit dose (UD) system allows minimisation of potential errors during prescription, preparation and therapy administration phases. In this context, the intervention of a pharmacist in clinical choices may optimise this process by assessing the appropriateness of prescriptions. At the time of UD therapy validation, the pharmacist takes part in the evaluation of the most appropriate therapeutic options through the inclusion of annotations on each individual prescription for each patient. Aim and objectives: The aim of this work was to demonstrate how the intervention of pharmacists in this process is essential for patient safety and improving clinical risk management. Material and methods: Therapies of all patients receiving the UD system in the period 1 March 2019 to 28 February 2020 were analysed, and all of the annotations included by the pharmacist were reviewed. The annotations were classified into seven subgroups, based on the type of potential errors identified regards: (1) duration of therapy; (2) dosage/frequency of administration; (3) interactions; (4) therapeutic indications; (5) method of reconstitution/dilution; (6) type of formulation; and (7) double prescriptions. These subgroups were further divided based on the potential risk of event/error, latent/active, and high and low risk (HR, LR) where high risk refers to potentially dangerous effects for patients. Results: In the observed period, 11 881 patients were admitted to the UD regimen, of whom 5414 carried one or more annotations by the pharmacist, requesting specific changes to the prescriptions. In particular, based on the indicated subgroups, 10 537 notes were inserted and divided as follows: Notes 1235; (HR) 531 (43%); (LR) 704 (57%) Notes 4558; (HR) 1595 (35%); (LR) 2963 (65%) Notes 2329; (HR) 2073 (89%); (LR) 256 (11%) Notes 192; (HR) 192 (100%); (LR) 0 (0%) Notes 1396; (HR) 1368 (98%); (LR) 28 (2%) Notes 603; (HR) 30 (5%); (LR) 573 (95%) Notes 224; (HR) 137 (61%); (LR) 87 (39%) From this analysis, 38% of prescriptions were modified as specifically indicated by the Pharmacist. Conclusion and relevance: This analysis demonstrated how the role of the pharmacist is critical in identifying potential errors that may occur at the time of prescription. This is necessary for minimising adverse effects for patients during specific therapeutic treatments. References and/or acknowledgements: Conflict of interest: No conflict of interest